Different Preliminary Feed on The Response of Growth And Sustainability of Betta Fish Larvae (Betta Splendens) - Yohana, Yohana; Tantu, Fadly Y; Madinawati, Madinawati (AgriSains, 2020)
Some problems in Betta splendens cultivate activities were slow growth and mortality rates still high in the larval stage. Generally, Betta splendens larvae require a feed type based to the larval mouth. Some types of feed that can be given for larvae were Infusoria and yolk suspension. The study aims to find out the growth and survival rate of Betta splendens giving different first feeding. The study was conducted in January-February 2019 at Laboratory of Water Quality and Aquatic Biota, Faculty of Animal Husbandry and Fisheries, Tadulako University. The study used a Completely Randomized Design consisting of 3 treatments: A (infusoria); B (egg yolk); C (infusoria and egg yolk). Data were analyzed with ANOVA. The results showed that giving different first feeding did not significantly affect the growth of Betta splendens. The highest weight in the treatment of infusoria feed and the highest percentage of survival rate in the treatment of egg yolk.